Computational approaches in cancer multidrug resistance research: Identification of potential biomarkers, drug targets and drug-target interactions - Tolios, A; De Las Rivas, J; Hovig, E; Trouillas, P; Scorilas, A; Mohr, T (Drug resistance updates, 2020)
Like physics in the 19th century, biology and molecular biology in particular, has been fertilized and enhanced like few other scientific fields, by the incorporation of mathematical methods. In the last decades, a whole new scientific field, bioinformatics, has developed with an output of over 30,000 papers a year (Pubmed search using the keyword "bioinformatics"). Huge databases of mass throughput data have been established, with ArrayExpress alone containing more than 2.7 million assays (October 2019). Computational methods have become indispensable tools in molecular biology, particularly in one of the most challenging areas of cancer research, multidrug resistance (MDR). However, confronted with a plethora of different algorithms, approaches, and methods, the average researcher faces key questions: Which methods do exist? Which methods can be used to tackle the aims of a given study? Or, more generally, how do I use computational biology/bioinformatics to bolster my research? The current review is aimed at providing guidance to existing methods with relevance to MDR research. In particular, we provide an overview on: a) the identification of potential biomarkers using expression data; b) the prediction of treatment response by machine learning methods; c) the employment of network approaches to identify gene/protein regulatory networks and potential key players; d) the identification of drug-target interactions; e) the use of bipartite networks to identify multidrug targets; f) the identification of cellular subpopulations with the MDR phenotype; and, finally, g) the use of molecular modeling methods to guide and enhance drug discovery. This review shall serve as a guide through some of the basic concepts useful in MDR research. It shall give the reader some ideas about the possibilities in MDR research by using computational tools, and, finally, it shall provide a short overview of relevant literature.
Keywords: lékové transportní systémy; chemorezistence; Antineoplastic Agents; Computational Biology; Drug Resistance, Neoplasm; Neoplasms; Drug Resistance, Multiple; protinádorové látky; lidé; Drug Delivery Systems; Biomarkers, Tumor; Animals; nádorové biomarkery; zvířata; Humans; nádory; mnohočetná léková rezistence; výpočetní biologie